Outpatient Cervical Ripening With Misoprostol to Prevent Post-Term Pregnancy: A Double-Blind Randomized Clinical Trial - Atiyeh Vatanchi; Sedighe Ayati; Leila Pourali; Masoumeh Mirteimouri; Mohammad Taghi Shakeri; Sara Partanezhad (Acta Medica Iranica, 2023)
Outpatient use of misoprostol is assessed in a few studies and usually in low doses and vaginal routes. This study aimed to evaluate cervical ripening by outpatient administration of misoprostol to prevent post-term pregnancy. This randomized clinical trial study was performed on 140 patients that were randomly allocated into two groups: 25 μg sublingual SL (group A) and 50 μg PO misoprostol (group B). The patients were primigravid with a gestational age of 40 weeks, with an amniotic fluid index (AFI) of ≥5 cm, a reactive non-stress test (NST) with no evident uterine contraction, Bishop Score of <8, and no notable past medical history. Patients who had a normal vaginal delivery before 41 weeks were considered successful delivery. Maternal age, the number of misoprostol doses, vaginal examination, type of interventions before delivery, the indication of hospitalization, delivery route, the indication of cesarean section, delivery complications, and neonatal outcomes were compared using SPSS software. P<0.05 was considered statistically significant. group A had mean age of 23.27±4.03 years and Group B had a mean age of 24.61±5.46 years with no significant difference (P=0.223). The number of misoprostol doses (P=0.001), extra misoprostol, and oxytocin application were significantly lower in group B (P=0.003). Maternal and neonatal complications showed no significant difference between the two groups (P>0.05). Outpatient cervical ripening with misoprostol appears to be an optimal method. More prospective studies with higher sample sizes are required to ensure its safety for routine recommendations for cervical ripening to prevent post-term pregnancy.